2019
DOI: 10.1016/j.molcel.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Imaging Uncovers Rules Governing Nonsense-Mediated mRNA Decay

Abstract: Summary Nonsense-mediated decay (NMD) is a surveillance system that degrades mRNAs containing a premature termination codon (PTC) and plays important roles in protein homeostasis and disease. The efficiency of NMD is variable, impacting the clinical outcome of genetic mutations. However, limited resolution of bulk analyses has hampered the study of NMD efficiency. Here, we develop an assay to visualize NMD of individual mRNA molecules in real time. We find that NMD occurs with equal probability duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
124
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(149 citation statements)
references
References 54 publications
(88 reference statements)
13
124
2
Order By: Relevance
“…NMD is a pervasive mechanism, influencing the expression of thousands of genes in humans (Mendell et al, 2004; Colombo et al, 2017); however, it is not a trivial matter to determine which transcripts are direct NMD targets and what features of a transcript trigger NMD. Studying the steady-state expression of transcripts after NMD inhibition has shown that exon-exon junctions located ≥50 nt downstream of a stop codon are potent triggers of NMD, while it is less clear as to what extent long 3’ UTRs act to trigger NMD (Lindeboom et al, 2016; Colombo et al, 2017; Tian et al, 2017; Lloyd et al, 2018; Hoek et al, 2019). By examining mutations in tumors and the corresponding changes in expression of these genes, it was shown that the EJC model was able to account for the majority of expression changes in mutations leading to early stop codons, and found that the length of the 3’ UTR was not a factor (Lindeboom et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NMD is a pervasive mechanism, influencing the expression of thousands of genes in humans (Mendell et al, 2004; Colombo et al, 2017); however, it is not a trivial matter to determine which transcripts are direct NMD targets and what features of a transcript trigger NMD. Studying the steady-state expression of transcripts after NMD inhibition has shown that exon-exon junctions located ≥50 nt downstream of a stop codon are potent triggers of NMD, while it is less clear as to what extent long 3’ UTRs act to trigger NMD (Lindeboom et al, 2016; Colombo et al, 2017; Tian et al, 2017; Lloyd et al, 2018; Hoek et al, 2019). By examining mutations in tumors and the corresponding changes in expression of these genes, it was shown that the EJC model was able to account for the majority of expression changes in mutations leading to early stop codons, and found that the length of the 3’ UTR was not a factor (Lindeboom et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…By examining mutations in tumors and the corresponding changes in expression of these genes, it was shown that the EJC model was able to account for the majority of expression changes in mutations leading to early stop codons, and found that the length of the 3’ UTR was not a factor (Lindeboom et al, 2016). In single molecule studies of transcripts, exon-exon junctions were found to be a potent trigger of NMD while the long 3’ UTRs tested were not (Hoek et al, 2019). In this study, we used the abundance of transcripts in the different polysome fractions to explore the features of transcripts linked to NMD.…”
Section: Discussionmentioning
confidence: 99%
“…To measure the fluorescence intensities over time on single mRNAs, we used a Matlab-based software package called 'TransTrack' that we have recently developed (Boersma et al, 2019). Using TransTrack, we tracked single mRNAs from the start of translation, measured the GFP fluorescence intensity of each 48 translation site and performed local background subtraction.…”
Section: Arrival Time Of the First Ribosome At The Sirna Binding Sitementioning
confidence: 99%
“…Because translation termination of a single ribosome cannot be readily distinguished from mRNA cleavage, as they both result in the separation of a single ribosome/SunTag array from the mRNA, we used mRNA disappearance (i.e. decay of the 3' cleavage fragment) as a read-out for mRNA cleavage (Hoek et al, 2019). Therefore, we determined the time from GFP appearance to mRNA disappearance for each mRNA molecule.…”
Section: Analysis Of Mrna Cleavage With the Emi1-kif18b Reportermentioning
confidence: 99%
“…An important feature of NMD is that it is dependent on translation, either on the first or a later round [9][10][11][12] . Evidence supporting the formation of complexes containing NMD and translation termination factors suggested a functional connection between the two processes [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%